Subacute Ruminal Acidosis and Evaluation of Blood Gas Analysis in Dairy Cow - Matteo Gianesella; Massimo Morgante; Chiara Cannizzo; Annalisa Stefani; Paolo Dalvit; Vanessa Messina; Elisabetta Giudice (Veterinary Medicine International)
Subacute Ruminal Acidosis (SARA) corresponds to an imbalance between lactate-producing bacteria and lactate-using bacteria, which results in a change in ruminal pH associated with a prevalent consumption of rapidly fermentable carbohydrates. In our study, 216 primiparus and multiparus dairy cows were selected from 20 Italian intensive dairy herds and were divided into three groups based on the risk of SARA. All the dairy cows had high average milk production. After blood sampling, a complete blood gas analysis was performed. One-way ANOVA was performed to compare the three groups. O2 Cont, PCO2, blood pH, O2Hb, urinary pH, and rumen pH were significantly lower in cows with rumen pH<5.5. These results indicate that blood gas analysis is a valuable tool to diagnose acidosis in dairy cows because it provides good assessment of acidosis while being less invasive than rumen pH analysis.